2014
DOI: 10.1089/ham.2013.1128
|View full text |Cite
|
Sign up to set email alerts
|

Early Adaption to the Antarctic Environment at Dome C: Consequences on Stress-Sensitive Innate Immune Functions

Abstract: As this early adaptation is not related to psychological stress, the changes observed are likely to be induced by environmental stressors, especially hypoxia. As hypoxia is triggering ATP-catabolism, leading to elevated endogenous adenosine concentrations, this and the increased catecholamine concentration might contribute to the early, but reversible downregulation of innate immune functions. This indicates the slope of innate immune adaptation to hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
1
21
0
4
Order By: Relevance
“…During the early adaptation phase (1 mo) of the Concordia winter-over crew in 2008, cortisol levels and stress questionnaires did not report higher stress levels. However, 24-h urinary catecholamine excretion was significantly increased (13).…”
Section: Antarctica a Testbed For Real Exploration Type Isolation Comentioning
confidence: 87%
“…During the early adaptation phase (1 mo) of the Concordia winter-over crew in 2008, cortisol levels and stress questionnaires did not report higher stress levels. However, 24-h urinary catecholamine excretion was significantly increased (13).…”
Section: Antarctica a Testbed For Real Exploration Type Isolation Comentioning
confidence: 87%
“…In a previous study, an increase of beta activity in the prefrontal cortex was observed after an acute hypoxic exposure (44). Even though a fast adaptation was shown (16), we cannot exclude that hypoxia might affect our results. In this study we had no baseline recordings before participants’ trip to Antarctica.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, the station is at high altitude (3200m) which implies that the crewmembers have to cope with lower oxygen levels (hypoxia) and low air pressure (hypobaria). Because of its location at the South Pole, the atmospheric pressure is equivalent to an altitude of 3800m outside the polar circle (16). Since the oxygen concentration is at 13% instead of the usual 21%, the blood saturation in oxygen is lower, which increase the heart rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao longo dos últimos 10 anos (2006 a 2017), foram publicados menos de 30 estudos especializados, conforme consulta às bases de dados Web of Science e SCOPUS. As publicações mais recentes focam em estresse e coping (Anton-Solanas, O'Neil, Morris & Dunbar, 2016;Barkaszi, Takács, Czigler & Balázs, 2016); aspectos relacionados ao sono e ao ciclo circadiano (Brockmann et al, 2017;Chen, Wu, Li, Zhang & Xu, 2016;Feuerecker et al, 2014;Morris, Pilcher, & Powell, 2017); e à adaptação ao ambiente polar (Jin, Touyama, Yamada, Yamazaki, & Benno, 2014;Najjar et al, 2014;Pattarini, Scarborough, Sombito, & Parazynski, 2016).…”
unclassified